PENGARUH PENGELUARAN PEMERINTAH SEKTOR KESEHATAN DAN PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI KOTA MEDAN - Diwayana Putri Nasution; Muhammad Toyib Daulay; Epi Handani (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
This study aims to analyze and determine government expenditure in the health and education sectors on economic growth through the human development index as an intervening variable. This study uses path analysis tools and time series data from 2010 to 2017 which are processed with the SPSS 16 application. This research uses descriptive and quantitative analysis methods. Public health sector expenditure is 0.322 smaller than the value of the indirect effect of 1.14, which means that government spending in the health sector has a significant effect on Economic Growth through the Human Development Index as an intervening variable in Medan City. The results of the second analysis show that the Education Sector Government Expenditure is 0.626 greater than the value of the indirect effect of 0.116, meaning that the Education Sector Government Expenditure has no effect on Economic Growth through the Human Development Index as an intervening variable in Medan City.